Diversification rates of the "Old Endemic" murine rodents of Luzon Island, Philippines are inconsistent with incumbency effects and ecological opportunity. (1st July 2018) - Rowsey, Dakota M.; Heaney, Lawrence R.; Jansa, Sharon A.
Abstract: Diversity‐dependent cladogenesis occurs when a colonizing lineage exhibits increasing interspecific competition as it ecologically diversifies. Repeated colonization of a region by closely related taxa may cause similar effects as species within each lineage compete with one another. This may be particularly relevant for secondary colonists, which could experience limited diversification due to competition with earlier, incumbent colonists over evolutionary time. We tested the hypothesis that an incumbent lineage may diminish the diversification of secondary colonists in two speciose clades of Philippine "Old Endemic" murine rodents—Phloeomyini and Chrotomyini—on the relatively old oceanic island of Luzon. Although phylogenetic analyses confirm the independent, noncontemporaneous colonization of Luzon by the ancestors of these two clades, we found no support for arrested diversification in either. Rather, it appears that diversification of both clades resulted from constant‐rate processes that were either uniform or favored the secondary colonists (Chrotomyini), depending on the method used. Our results suggest that ecological incumbency has not played an important role in determining lineage diversification among Luzon murines, despite sympatric occurrence by constituent species within each lineage, and a substantial head start for the primary colonists.